An efficient sensor integrated model for hosting real-time data monitoring applications on cloud. (2018) - Yadav, N. Sudhakar; Reddy, B. Eswara; Srinivasa, K.G.
Wireless sensor networks (WSNs) have become an integral part of healthcare monitoring applications and also using in a wide range of domains such as environmental monitoring, healthcare, asset monitoring modern warfare scenarios, industrial and production monitoring. A number of solutions have been proposed so far which provides assimilation of data on an hourly basis and the capability of sensors are approximated to almost ideal situation. With the exploration and advancement in the field of internet of things (IoT), the focal point has shifted towards the interoperability of WSNs and a cloud-based central data repository which collaborates and comprehends a uniquely identifiable internet like structure. This bottom up internet-like structure has paved the way for a sensor integrated cloud-based architecture REALSENSE. This paper provides a detailed run down on the REALSENSE architecture which integrates WSN with Internet of Things in a robust efficient approach. Using the REALSENSE architecture, a set of real-time applications can be deployed, some of them are illustrated in this paper.